In my HW, I can see that the following statement

"No student in this class has sent e-mail to exactly two other students in this class."

can be expressed as follows

$$¬∃x∃y∃z(y \neq z ∧x \neq y ∧x \neq z ∧ ∀w(w \neq x ⇒ (E(x, w) ⇔ (w = y ∨ w = z))))$$

But my initial thought was this:

$$\neg \exists x \exists!y\exists!z((x \neq z) \land (x \neq y)\land(y \neq z)\land Email(x,y) \land Email(x,z))$$

Is my initial thought incorrect, and if so what is wrong with it?


1 Answer 1


It's not correct. The first thing that strikes me is that if $y$ is unique, then how can you say $z$ is unique when it has the same property as $y$? Clearly they're not unique. The pair is what you want unique.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.